2014
DOI: 10.1016/j.pmrj.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Botulinum Toxin Type A in the Management of Neonatal Brachial Plexus Palsy

Abstract: BoNT-A is an effective adjunct to therapy and surgery in managing muscle imbalance, cocontractions, and contractures in neonatal brachial plexus palsy. Use of BoNT-A can result in averting, modifying, or deferring surgical interventions in a number of affected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 30 publications
1
48
0
10
Order By: Relevance
“…Patients with incomplete medical records or <1-year follow-up were excluded. [5][6][7] Patients with concomitant or prior shoulder surgery, or microsurgery within 8 months, 5 were excluded. Two patients underwent repeat closed reductions and only their initial attempts were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with incomplete medical records or <1-year follow-up were excluded. [5][6][7] Patients with concomitant or prior shoulder surgery, or microsurgery within 8 months, 5 were excluded. Two patients underwent repeat closed reductions and only their initial attempts were included.…”
Section: Methodsmentioning
confidence: 99%
“…4 Few recent studies have investigated outcomes after BTX-A, closed reduction, and spica cast immobilization in children with early posterior shoulder subluxation. [4][5][6] The purpose of this study was to review our experience with this treatment method to report success rates and determine pretreatment predictors of success.…”
mentioning
confidence: 99%
“…One study suggested that BTI might be useful to reduce posterior subluxation or dislocation of the shoulder in babies with BPBI 22. BTI could also improve passive and active shoulder ROM and functional capacity 20 23 24. BTI is a minimally invasive treatment that is well tolerated in young children 25.…”
Section: Introductionmentioning
confidence: 99%
“…BTI is a minimally invasive treatment that is well tolerated in young children 25. When used prior to surgery, it could avert or reduce the complexity of surgical secondary orthopaedic procedures (eg, subscapularis release, latissimus dorsi and teres major transfers) 22 23. Although the results of studies of early BTI for BPBI are encouraging, most studies are retrospective, include small samples and do not have a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the full extent and pattern of shoulder muscle atrophy in OBPP is not well established. The lack of information related to the pectoralis major (PM) and teres major (TM) is a major deficit when developing treatments for children with OBPP, as these muscles are often targeted for lengthening, transfer procedures 1317 or botulinum toxin injections 18,19 . Thus, a more complete understanding of the pattern and degree of muscle atrophy across shoulder muscles in patients with OBPP is needed to improve interventional outcomes.…”
Section: Introductionmentioning
confidence: 99%